Integration Management of the National Curriculum and Cambridge Curriculum in Improving the Quality of Education - Anggraini, Selvia; Marno, Marno; Efiyanti, Alfiana Yuli (Universitas Sang Bumi Ruwa Jurai, 2025)
This research aims to investigate the management of integrating the National Curriculum and the Cambridge Curriculum to improve the quality of education in schools. The study employs a qualitative research methodology, utilizing a combination of structured interviews, observations, and document analysis as data collection techniques. The analytical framework is based on the interactive and continuous approach proposed by Miles and Huberman, which emphasizes data condensation, presentation, and conclusion drawing to ensure a comprehensive understanding of the findings. The results of the study indicate that successful integration of the two curricula hinges on several critical factors, including the alignment of educational objectives, the professional development of educators, and the availability of adequate resources and infrastructure. The research highlights that educators must possess a deep understanding of both curricula to effectively implement an integrated approach that meets the diverse needs of students. Furthermore, the findings suggest that fostering a collaborative environment among teachers is essential for sharing best practices and enhancing pedagogical strategies. Additionally, the study reveals that the integration process not only enhances the educational experience for students but also significantly improves their competitiveness in both national and international contexts. The research underscores the importance of continuous evaluation and adaptation of the integration strategies to respond to the dynamic nature of educational demands.